Indian cinema, the Bollywood saga - Raheja, Dinesh; Kothari, Jitendra (New Delhi : Lustre Press/Roli Books, 2004)
Articles on history of Hindi motion pictures
Keywords: Motion pictures -- India -- History; Motion picture actors and actresses -- India